2021
DOI: 10.1039/d1nr03484g
|View full text |Cite
|
Sign up to set email alerts
|

How size, shape and assembly of magnetic nanoparticles give rise to different hyperthermia scenarios

Abstract: The use of magnetic nanoparticles (MNPs) to locally increase the temperature at the nanoscale under the remote application of alternating magnetic fields (magnetic particle hyperthermia, MHT) has become an important...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 66 publications
2
63
0
Order By: Relevance
“…The aggregation condition of both iMS and cMS may interfere with tumor cellular endocytosis, affecting iMS and cMS inhibition on tumor cells . Furthermore, given the situation that the iMS and cMS only interact with tumor cells and are not endocytosed by them, the aggregation state reduces heat production in the above-mentioned magnetic hyperthermia process . When treated with N2a cancer cells, undamaged and spiroid AMB-1 cells exhibited outstanding dispersion (Figure d and inset).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aggregation condition of both iMS and cMS may interfere with tumor cellular endocytosis, affecting iMS and cMS inhibition on tumor cells . Furthermore, given the situation that the iMS and cMS only interact with tumor cells and are not endocytosed by them, the aggregation state reduces heat production in the above-mentioned magnetic hyperthermia process . When treated with N2a cancer cells, undamaged and spiroid AMB-1 cells exhibited outstanding dispersion (Figure d and inset).…”
Section: Resultsmentioning
confidence: 99%
“…During the process of magnetic hyperthermia, magnetic materials and their dispersion are critical to heating production. , To assess the heating efficiency of intact AMB-1 cells, we first used an AMF with a frequency of 518 kHz and a strength of 16 kA/m to act on MTB AMB-1 cells with varying magnetosome content for 30 min. The temperature created by intact AMB-1 cells under the AMF increased over time, as illustrated in Figure a.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the investigated CoFe Finally, not only the chemical composition of MNPs determines their biocompatibility and heating effectiveness, but also MNPs shape and size. It was shown that depending on shape (spheres, cubes, rods, flowers, discs, etc.,) iron oxide MNPs demonstrate different SLP values [2,43]. For example, if we compare iron oxide MNPs of similar magnetic volumes but various shapes, their effectiveness for MHT (SLP) decreases in the following order: nanorods-cubes-spheres.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasmall IONPs (<10 nm) have a superparamagnetic behavior but a poor thermal conversion efficiency (Chang et al, 2018). Current MHT uses IONPs with core sizes around 10 to 15 nm, which are adequate sizes for the development of theranostic IONPs (Chang et al, 2018; Gavilan et al, 2021).…”
Section: Magnetic Ionps Mediated Magnetic Hyperthermia Therapy and Ph...mentioning
confidence: 99%